Adopting Global Lung Function Initiative Reference Equations Alters Pulmonary Function Testing Interpretation in a Safety-Net Cohort - Stephen T. Russell; Jenny E. Han; Jordan A. Kempker; Eric Honig; Abiodun T Kukoyi (The Open Respiratory Medicine Journal, 2026)
Introduction/Objective Current American Thoracic Society/European Respiratory Society (ATS/ERS) guidelines recommend Global Lung Initiative (GLI) reference equations for spirometry, lung volumes, and Diffusing Capacity of the Lungs for Carbon Monoxide (DLCO). The impact of adopting these reference equations remains unclear and may differ by race. Methods We conducted a cross-sectional study of Pulmonary Function Tests (PFT) performed at Grady Memorial Hospital in Atlanta, GA, from 2017 to 2024. PFT components and interpretive patterns were analyzed using current Grady reference equations, then compared with GLI, including race-neutral spirometry, and stratified by race. Results There were 7877 eligible patients; 7034 (89%) were Black, 529 (7%) were White, and 314 (4%) were Hispanic. Black patients had increased frequency of abnormal FEV1 (37.4% to 52.1%, p < 0.001), FVC (32.4% to 48.4%, p < 0.001), Total Lung Capacity (TLC) (6.7% to 40.8%, p < 0.001), and DLCO (30.3% to 45.3%, p < 0.001). White and Hispanic patients had decreases in abnormal FEV1 (48.0% to 38.0%, p < 0.001, and 29.0% to 20.7%, p < 0.001, respectively), decreases in abnormal FVC (38.0% to 26.1%, p < 0.001, and 26.1% to 18.2%, p < 0.001), increases in abnormal TLC (12.7% to 17.8%, p < 0.001, and 12.4% to 16.8%, p < 0.001) and no change in DLCO. 44.3% of Black, 16.8% of White, and 14.5% of Hispanic patients had a new interpretive pattern. Discussion In this health system with a predominantly Black patient population, transitioning our PFT reference equations to GLI increased detection of abnormalities and changed interpretive patterns, with greater effects in Black patients. Conclusion The health-system impact of implementing GLI reference equations is highly context-dependent, influenced by demographics and prior reference equations.